Pre-disaster investment decisions for strengthening a highway network - Peeta, Srinivas; Sibel Salman, F.; Gunnec, Dilek; Viswanath, Kannan (Computers & operations research, 2010)
We address a pre-disaster planning problem that seeks to strengthen a highway network whose links are subject to random failures due to a disaster. Each link may be either operational or non-functional after the disaster. The link failure probabilities are assumed to be known a priori, and investment decreases the likelihood of failure. The planning problem seeks connectivity for first responders between various origin–destination (O–D) pairs and hence focuses on uncapacitated road conditions. The decision-maker's goal is to select the links to invest in under a limited budget with the objective of maximizing the post-disaster connectivity and minimizing traversal costs between the origin and destination nodes. The problem is modeled as a two-stage stochastic program in which the investment decisions in the first stage alter the survival probabilities of the corresponding links. We restructure the objective function into a monotonic non-increasing multilinear function and show that using the first order terms of this function leads to a knapsack problem whose solution is a local optimum to the original problem. Numerical experiments on real-world data related to strengthening Istanbul's urban highway system against earthquake risk illustrate the tractability of the method and provide practical insights for decision-makers.